Interpretation of BUMN Losses as State Financial Losses in Corruption Crimes from the Perspective of Legal Certainty - Danang Yudanto; Prija Djatmika; Abdul Madjid (JURNAL AKTA, 2026)
This study aims to analyze the interpretative construction of losses in State-Owned Enterprises (BUMN) as state financial losses in corruption cases and to formulate an interpretation model that ensures legal certainty. This research employs a normative juridical method using statutory, conceptual, and case approaches, particularly focusing on court decisions involving BUMN. The findings indicate that the main issue does not lie in conflicting norms, but rather in the inconsistency of interpretative methods applied by law enforcement authorities. In many cases, law enforcement tends to adopt a result-based approach, emphasizing financial loss outcomes without adequately considering the underlying business decision-making process and the application of the business judgment rule. This approach often leads to the misclassification of legitimate business risks as criminal acts, thereby creating legal uncertainty and discouraging strategic decision-making within BUMN. Furthermore, such inconsistencies may undermine corporate governance and reduce confidence among BUMN directors in making business decisions. Therefore, this study provides practical contributions by offering clear guidelines for law enforcement in distinguishing between business risks and corrupt actions. It also serves as a reference for policymakers in harmonizing legal frameworks related to BUMN governance and anti-corruption regulations. The novelty of this research lies in proposing a structured interpretation model that integrates normative, contextual, and causality-based approaches to define clear boundaries between BUMN losses and state financial losses.